KEPEMIMPINAN DEMOKRATIS DALAM PENERAPAN MANAJEMEN BERBASIS SEKOLAH - Reresi, Marsianus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2018)
This article presents the conceptual study of the democratic leadership role of principals in the implementation of school-based management. This study is very relevant because this study presents alternative leadership of school principals as the main factor in the successful implementation of school-based management.